2021
DOI: 10.1101/2021.04.06.438634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasma microbiome in COVID-19 subjects: an indicator of gut barrier defects and dysbiosis

Abstract: The gut is a well-established route of infection and target for viral damage by SARS-CoV-2. This is supported by the clinical observation that about half of COVID-19 patients exhibit gastrointestinal (GI) symptoms. We asked whether the analysis of plasma could provide insight into gut barrier dysfunction in patients with COVID-19 infection. Plasma samples of COVID-19 patients (n=30) and healthy control (n=16) were collected during hospitalization. Plasma microbiome was analyzed using 16S rRNA sequencing, metat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 79 publications
(32 reference statements)
2
27
0
Order By: Relevance
“…Components of abnormal microbiota in blood were found in almost 65% of patients. The predominance of Gram-negative microorganisms was noted in the study, which also accounted for the increased serum LPS levels found, in comparison with a control group of healthy individuals [ 103 ].…”
Section: Intestinal Infections and Antibiotic Therapymentioning
confidence: 94%
“…Components of abnormal microbiota in blood were found in almost 65% of patients. The predominance of Gram-negative microorganisms was noted in the study, which also accounted for the increased serum LPS levels found, in comparison with a control group of healthy individuals [ 103 ].…”
Section: Intestinal Infections and Antibiotic Therapymentioning
confidence: 94%
“…A recent study by Prasad et al. measured several markers of gut permeability in the plasma ( 60 ). Levels of FABP2, PGN, and LPS were significantly higher among COVID-19 patients compared to healthy subjects, suggesting translocation of pro-inflammatory antigens from a leaky gut.…”
Section: Role Of Gut Microbiota In the Pathogenesis Of Covid-19mentioning
confidence: 99%
“…Consequently, a number of studies using DNA (16S rRNA) sequencing have investigated the origin of the "blood microbiome", indicating that the blood microbiome of healthy individuals comprises of DNA originating from mainly Proteobacteria, Actinobacteria, Firmicutes, and Bacteroidetes [23], although the source of this circulating DNA is often not described. BEV-associated DNA has been identified in patients with Alzheimer's disease [24], Parkinson's disease [25], dermatitis [26], asthma [27], cardiovascular disease [28], gastric cancer [29], biliary tract cancer [30], and COVID-19 [31]. However, few have investigated the origin of blood-derived BEVs in IBD.…”
Section: Introductionmentioning
confidence: 99%